Development of Geographic Information System (GIS) Distribution of Triple Elimination Implementation in Pregnant Women at Kramatjati Health Center: Pengembangan Geographic Information System (GIS) Distribusi Pelaksanaan Triple Eliminasi Pada Ibu Hamil di Puskesmas Kramatjati - Utami, Febi Puji; Ibrahim, Rohayati; Susilawati, Dewi (Universitas Mohammad Husni Thamrin, 2025)
Background: The development of this GIS was carried out to reduce or overcome the weakness of this unattainability due to uncontrolled distribution of data on pregnant women/mapping of pregnant women who had undergone Triple Elimination examinations in the Kramatjati Community Health Center area, which has 7 sub-districts, 65 RWs and 653 RTs. With so many areas that the Kramatjati Community Health Center is responsible for, it cannot rely on manual data collection or bookkeeping alone. Objective: Designing the Development of GIS (Geographic Information System) Distribution for the Implementation of Triple Elimination of Pregnant Women at the Kramatjati Community Health Center. Research Method: This type of research uses quantitative research, using a Research and Development (R&D) research design. The research period is March 2024 at the Kramatjati Community Health Center. With a total population of 16 people. The sampling technique uses total sampling. The analysis used is univariate analysis using frequency distribution. Research Results: Based on the SUS (System Usability Scale), the SUS score was 77.3. Therefore, it can be concluded that the Acceptability Range results are declared Acceptable, Grade Scale: C, Adjective Rating is declared Excellent, and Percentiles are in the Good category. Conclusion: The results of system testing to determine the usefulness of GIS development in analyzing the distribution of Triple Elimination implementation for pregnant women at the Kramatjati Community Health Center using the (SUS) method resulted in an average score of 77.3 in the Good category. The results of the feasibility test from 16 respondents showed that 10 people (62.5%) stated that they were quite feasible. Suggestion: It is hoped that it can be developed in further research by designing and integrating it into advanced systems, or by adding variables or additional data analysis.